1999
DOI: 10.1055/s-1999-57
|View full text |Cite
|
Sign up to set email alerts
|

The Histological Basis of Detection of Adenoma and Cancer in the Colon by Autofluorescence Endoscopic Imaging

Abstract: The reason for the decreased fluorescence in diseased tissues appears to be a decrease in collagen fluorescence due to the screening effect of mucosal thickening or replacement of submucosa by cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…4(a), data shown for two specimen pairs]. This is consistent with prior literature, which indicates that fluorescence emission decreases in colonic adenoma and carcinoma, 29,53 as well as cancer progression in bronchial and oral mucosa. 27,30 However, fluorescence resulting from excitation at higher wavelengths was increased, and in the S4 sample was higher than normal tissue [Figs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…4(a), data shown for two specimen pairs]. This is consistent with prior literature, which indicates that fluorescence emission decreases in colonic adenoma and carcinoma, 29,53 as well as cancer progression in bronchial and oral mucosa. 27,30 However, fluorescence resulting from excitation at higher wavelengths was increased, and in the S4 sample was higher than normal tissue [Figs.…”
Section: Resultssupporting
confidence: 90%
“…[32][33][34][35][36] In general, the autofluorescence intensity of cancerous and precancerous lesions is lower, due to mucosal thickening and reduced collagen fluorescence. 29 However, tissue autofluorescence has been attributed to many sources, 37 including metabolic molecules (NADH, FAD), [38][39][40] proteins, and other molecules (flavins, collagen, elastin, hemoglobin), 41 breakdown of certain biomolecules (hematoporphyrin, flavins), 42 and induced molecular changes concurrent with inflammation. [43][44][45] Hence, the molecular and histologic basis for AFI is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The main source of autofluorescence eruption under blue light excitation has been considered to be submucosal collagen, not the mucosal layer in human (Izuishi et al, 1999;Huang et al, 2004). In this report, we describe a rare case in which highly fluorescent mucosal macrophages made a superficial-type colonic adenoma remarkably easy to detect.…”
Section: Introductionmentioning
confidence: 85%
“…It is reported that the main source of tissue fluorescence is submucosal collagen and that the autofluorescence of the mucosal layer is weak in human, although the mucosal layer is the important source of autofluorescence in rat colons (Izuishi et al, 1999;Huang et al, 2004;Nakano et al, 2008;Nakano et al, in press). The attenuated autofluorescence in neoplastic lesions has been believed to be caused by a decrease in submucosal collagen-fluorescence due to the masking effect of mucosal thickening by neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In AFI images, almost all tumors with an elevated appearance (elevated type) were purple, while most of the tumors with a depressed appearance (depressed type) were green. Although endogenous fl uorophores exist in both the mucosa and the submucosa, collagen in the submucosa discharges a strong green autofl uorescence [8]. AFI images differ according to the autofl uorescence properties of the tissue, and the intensity of light, in particular, affects the AFI color.…”
Section: Discussionmentioning
confidence: 99%